Intelligence Disclosure and Cooperation in Repeated Interactions - Marco Lambrecht; Eugenio Proto; Aldo Rustichini; Andis Sofianos (Institute of Labor Economics (IZA), 2022)
We investigate in a laboratory setting whether revealing information on the intelligence of both players affects behavior in repeated games. We study the Prisoners' Dilemma (PD) and Battle of Sexes (BoS) as they cover a large set of the interesting scenarios generated by repeated games of two actions two players symmetric stage games. Furthermore, in order to understand how cognitive skills disclosure interacts with different potential payoff allocations, we consider two versions of the BoS, with high and low payoff inequality. In PD, disclosure markedly hampers cooperation, as higher intelligence players trust their partners less when made aware that they play against someone of lower ability than themselves. Similarly, in BoS with low payoff inequality, disclosure disrupts coordination, as higher intelligence players try to force their most preferred outcome. However, in the BoS with high payoff inequality, this pattern of behavior changes substantially. Disclosure does not significantly affect coordination, while coordination is more often on outcomes that favor the less intelligent player. This result may indicate an intention to achieve a fairer division, or that the intelligent player anticipates that the other player will not concede.
Keywords: C73; C91; C92; D83; 330; repeated prisoners dilemma; cooperation; intelligence; IQ